Re-Evaluation of Acid-Base Prediction Rules in Patients with Chronic Respiratory Acidosis. Issue 6 (3rd September 2003) - Martinu, Tereza; Menzies, Dick; Dial, Sandra
Abstract : RATIONALE: The prediction rules for the evaluation of the acid-base status in patients with chronic respiratory acidosis, derived primarily from an experimental canine model, suggest that complete compensation should not occur. This appears to contradict frequent observations of normal or near-normal pH levels in patients with chronic hypercapnia. METHODS: Linear regression analysis was used to estimate the relationships between arterial pH, bicarbonate and partial pressure of carbon dioxide (PCO2 ) from 18 separate arterial blood gas measurements in 18 clinically stable outpatients with chronic hypercapnic respiratory failure from chronic obstructive lung disease, and without clinical conditions or medications likely to cause a primary metabolic alkalosis. RESULTS: The PCO2 ranged from 45 mmHg to 77 mmHg, and pH ranged from 7.37 to 7.44. In only three of the arterial blood gas measurements were the pH values lower than 7.38. From the regression equations derived from these measurements, the pH decreased by 0.014 for each 10 mmHg increase in the PCO2, and the bicarbonate level increased by 5.1 mmol/L. These values are quite different from a decrease in pH of 0.03 and an increase in bicarbonate of 3.5 mmol/L predicted using the rules derived from the canine model. CONCLUSIONS: In patients with chronic stable hypercapnia, acid-base compensatory mechanisms appear to be more effective than would be predicted using the classic rules.